The Influence of Digital Marketing on the Understanding, Skills, Implementation and Performance of MSMEs Moderated by Constraints - Katri Gentari; Sri Agustina; Ika Rakhmalina; Heriyana Heriyana; Avisa Calista; Emelda Emelda (Penerbit Goodwood, 2026)
Purpose: This study aims to analyze in depth the effect of digital marketing training on improving understanding, skills, and the performance of MSMEs, with constraints as a moderating variable. The background of this research is based on the condition of MSMEs in Musi Banyuasin Regency, which face significant challenges in digital adaptation, such as limited digital literacy, insufficient promotional capital, and uneven internet access across regions. Methodology/Approach: This study employs a quantitative approach using a Likert-scale questionnaire distributed to 121 MSME participants of digital marketing training, along with secondary data obtained from the Office of Cooperatives and MSMEs of Musi Banyuasin Regency. Data analysis was conducted through reliability testing and regression analysis to examine both direct and moderating effects. Results/Findings: The results indicate that digital marketing training does not have a significant effect on understanding (Y1) and skills (Y2), but has a significant effect on MSME performance (Y3). The constraint factor was found to act as a moderating variable that weakens the relationship between digital marketing training and the dependent variables. Conclusions: Digital marketing training can enhance MSME performance even though it does not directly improve understanding and skills. These findings highlight the importance of tiered digital marketing training programs and continuous mentoring to ensure sustainable learning outcomes. Limitations: This study is limited to a quantitative approach and the geographic area of Musi Banyuasin Regency, thus the findings cannot yet be generalized broadly. Contribution: This research enriches the literature on the influence of digital marketing training on MSME performance and provides practical implications for local governments in strengthening digital capacity and competitiveness of MSMEs in the digital economy era.